How Much History is in the Passion Narratives?: Violence, Ideology, Historicity, and the Seditious Jesus Hypothesis - Middleton, Paul (Journal for the study of the historical Jesus, 2025)
This article reviews Fernando Bermejo-Rubio’s monograph, They Suffered under Pontius Pilate: Jewish Anti-Roman Resistance and the Crosses at Golgotha (2023). This book is the latest publication arguing for the ‘seditious Jesus’ hypothesis, the idea that Jesus was an armed revolutionary. It is argued that the volume rightly critiques some theological tendency in New Testament scholarship to downplay or ignore violence inherent in the Jesus tradition, but the argument that the men crucified with Jesus were either some of his disciples or sympathetic to his violent cause fails to convince. Despite arguing for historical minimalism in relation to the Gospel material, Bermejo-Rubio builds his case on the material he judges to be historical, but that is better explained by the imagination of the evangelists.